Online grocery shopping: the affect of time availability on Malaysian consumer preferences - Md. Zaini, Zetty Madina; Ramli, Noorazlin; Abd Ghani, Fatimah; Samsudin, Azlina; Hamid, Munirah; Jusoff, Kamaruzaman; Ngali, Norzaidah; Rahmat, Norazlina; Khalid, Khazainah; Musa, Mushaireen (IDOSI Publications, 2011)
Online grocery shopping is a new way of buying desired grocery products for household consumption. It has been started in Malaysia few years back with early local online grocer such as PasarBorong.com, SubangGrocer.com, CGdeMart.com and Citrasspicemart.com. Due to the advancement of today technology, online grocery shopping is gaining their market share in the food retail industry in Malaysia. Therefore, this study examined the perceptions and preferences of Malaysian consumers towards online grocery shopping. It is also examines three (3) important factors in online grocery shopping; cost and charges, time availability and convenience of online grocery shopping, which will contribute to the impact of online grocery shopping. Sample of population for this study were consumers who had some experience in online food retailing, particularly online grocery shopping and also those who have not yet to use internet to purchase grocery products. The researcher used self administered questionnaire and applied quota sampling in this study to represent three main ethnic in Malaysia (Malay, Chinese and Indian). Result of the study showed that Malaysian consumers were disagreeing on the extra cost and charges of online grocery shopping charged by the online grocers. The same feeling they expressed on the time availability that they have and also the time used to navigate the online pages. Most of the respondents were strongly disagree to have a repeat purchase for buying grocery product online. Therefore, the overall findings highlighted some important points which should be useful to the online grocers in order for them to capture the market and also to have repeat business in the future. It also helps the online grocers to understand consumers’ needs and preferences in online grocery shopping. By acknowledging this study, online grocers are able to position themselves in the market at par to be accepted by Malaysian consumers.